Information Access Evaluation. Multilinguality, Multimodality, and Visualization 4th International Conference of the CLEF Initiative, CLEF 2013, Valencia, Spain, September 23-26, 2013. Proceedings - Forner, Pamela; Müller, Henning; Paredes, Roberto; Rosso, Paolo; Stein, Benno (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed proceedings of the 4th International Conference of the CLEF Initiative, CLEF 2013, held in Valencia, Spain, in September 2013. The 32 papers and 2 keynotes presented were carefully reviewed and selected for inclusion in this volume. The papers are organized in topical sections named: evaluation and visualization; multilinguality and less-resourced languages; applications; and Lab overviews.